Kelayakan E-LKPD Interaktif Berbasis Nature of Science (NoS) untuk Melatihkan Keterampilan Berpikir Kritis Peserta Didik pada Materi Ikatan Kimia - Annisa Putria Dewitasari; Rusmini Rusmini (Jurnal Penelitian Pendidikan IPA, 2023)
The Merdeka Curriculum is adaptive and focuses on developing the character of the Pancasila Student Profile, one of which is critical thinking. This study aims to describe the feasibility of products, including the validity, practicality, and effectiveness of Nature of Science (NoS)-based e-LKPD on chemical bond materials. NoS learning has 6 pedagogical practices, namely background readings, case study discussions, inquiry lessons, inquiry labs, historical studies, and multiple assessments. Indicators of critical thinking skills trained in this study are analysis, explanation, and evaluation. This type of research is R&D research with 4D methods (Define, Design, Develop, and Disseminate), only up to the development stage but still tested on a limited basis. The results of the validity of the contents and constructs obtained were 98.70% and 99.26%, with very valid categories. The results of the practicality received a score of 94.95% in the very practical category. In terms of effectiveness, the average n-gain score of learning outcomes was obtained, the components of critical thinking skills in the analysis, evaluation, and explanation of students were 0.62, 0.54, 0.46, and 0.55 in the medium category. The n-gain score is obtained â‰¥ 0.3, so e-LKPD is effectively used to train students' critical thinking skills. It can be concluded that the developed e-LKPD is feasible for use.